O existencialismo no romance As i lay dying, de William Faulkner: estudo dos personagens Darl, Jewel e Addie Bundren - Ferreira, Denilson Amancio (2021)
The present research work shows an analysis of the characters Darl and Jewel Bundren, from the novel As I Lay Dying(1930), by William Faulkner. In this novel, the author presents an intimate perspective on the culture of the rural people of the southern United States. From this, he elaboratesa particular aesthetic, which reinvents the imaginary of those individuals: Southern Gothic. Through the Gothic heritage, present in the setting and movement of the narrative, we can see that the work develops a philosophical problem, concerning the existence and life of the individuals present there. The trajectory of the brothers throughout the narrative exposes their actions and reactions to a grotesque and violent atmosphere, indicating, every now and then, representations of idealistic and realistic thoughts. However, as it is narrated in monologues, which fragment the linearity of the story and present different versions of the same reality, the reflections of the characters are characterized as the main element that defines their attitudes towards their lives. Thus, starting from the travel novel, in Mikhail Bakhtin (2011), we try to read As I Lay Dyingfrom the idea of organicity of the genre defined by critics specialized in literature and in southern history, such as Cleanth Brooks (1969), Joel Williamson (1993) and Jay Watson (2019), Faulkner scholars. Consequently, David Punter and Glennis Byron (2004), and Bridget Marshall (2013) helpedus to understand and define the aesthetic of the Southern Gothic present in the novel. With this perspective in focus, we were able to draw a parallel among Faulkner, the southern people and Modernism, which helped us to understand why Faulkner’s text is so complex and makes it possible to raise so many philosophical questions. Based on philosophy, we sought to understand the construction of Darl and Jewel Bundren in a structure of representative opposition –one tending to idealism and the other to realism, respectively. JeanPaul Sartre’s (1970) existentialism provided the main basis for exploring philosophical thinking in relation to the condition of existence, as well as the only possible connection between the brothers, their mother, Addie Bundren. Finally, we understand that the critical readings of the novel awaken new interpretations of Faulkner’s text, as well as assist in the understanding of important universal themes, such as thepossiblephilosophical stancesin relation to existence, in addition to pointing out other questions that may be asked from the noveland from this work.